Resistant in‐stent restenosis in the drug eluting stent era. Issue 5 (17th May 2016) - Theodoropoulos, Kleanthis; Mennuni, Marco G.; Dangas, George D.; Meelu, Omar A.; Bansilal, Sameer; Baber, Usman; Sartori, Samantha; Kovacic, Jason C.; Moreno, Pedro R.; Sharma, Samin K.; Mehran, Roxana; Kini, Annapoorna S.
Abstract : Background: In the drug eluting stent (DES) era, repeat in‐stent restenosis (ISR) of the same coronary lesion, despite percutaneous coronary intervention (PCI), is a rare but challenging problem that has not been reported. We aim to describe what we propose as the occurrence of "resistant"‐ISR (R‐ISR) in the DES era, including angiographic patterns and outcomes. Methods: We defined R‐ISR as the recurrence of an ISR episode after successful treatment of the same lesion. We identified 276 consecutive patients with 291 lesions who had R‐ISR between May 2003 and June 2012. Quantitative coronary angiography (QCA) was performed for the first and second ISR episodes. Outcomes at one year, including death, myocardial infarction (MI), and target lesion failure (TLF), were analyzed. Results: Patients with R‐ISR had a high frequency of diabetes (62%), chronic kidney disease (39%), bifurcation lesions (51%), and moderate to severe calcified lesions (52%). The most common pattern of R‐ISR was focal (77%). R‐ISR lesions were treated with DES implantation (55%) or balloon‐only strategy (45%). The mortality rate and TLF at 2‐years were 9.3% and 51% respectively. The overall 2‐year TLF rate did not vary with the originally implanted stent, angiographic pattern (focal versus diffuse), or revascularization strategy. Conclusions: R‐ISR appears to consist predominantly of focal lesions and occurs in patients at high clinical and angiographic risk, conceivably owing to their unique diabetic and coronary calcification profile. Clinical outcomes are suboptimal irrespective of angiographic pattern or treatment strategy, indicating the recalcitrant nature of the disease, and need for aggressive treatment of cardiovascular risk factors and novel interventional approaches. © 2016 Wiley Periodicals, Inc.